2018
DOI: 10.1002/chir.22840
|View full text |Cite
|
Sign up to set email alerts
|

Solvent polarity effects on supramolecular chirality of a polyfluorene‐thiophene copolymer

Abstract: This study demonstrates the supramolecular chirality control of a conjugated polymer via solvent polarity. We designed and synthesized a chiral polyfluorene-thiophene copolymer having two different chiral side chains at the 9-position of the fluorene unit. Chiral cyclic and alkyl ethers with different polarities were selected as the chiral side chains. The sign of the circular dichroism spectra in the visible wavelength region was affected by the solvent system, resulting from the change of supramolecular stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
(82 reference statements)
0
4
0
Order By: Relevance
“…Because a phenylene spacer between two thiophene units does not introduce any tilt angle or deviation from planarity, aggregate ECD spectra of thiophene/phenylene copolymers are similar to those of already described PTs; they are dominated by exciton couplings between substantially planar polymer chains, although with less pronounced vibrational structure than PTs. Instead, aggregate ECD spectra of poly­( p -phenyleneethynylene- alt -bithiophene)­s resemble those of PPEs, with the characteristic sequence of several sharp bands due to the exciton coupling between vibronic excitations . In 2012, a series of axially chiral 1,1′-binaphthyl-thiophene copolymers were synthesized and investigated as drop-casted films by Goto et al, while Hirahara and colleagues focused the attention on alternating fluorene-thiophene copolymers, reporting dissymmetry factor g abs values up to 0.3 for pristine spin-coated samples; these giant ECD should be ascribed to the same extrinsic phenomena described above for poly­(fluorene)­s (section ). More recently, Bazan and co-workers described an alternating copolymer with thiophene or cyclopentadithiophene units and benzotriazole units bearing enantiopure ( S )-2-ethylhexyl chains, which showed maximum g abs factor of −0.008 at 665 nm in thin films prepared by drop casting of a chlorobenzene solution .…”
Section: Ecd Properties In Thin Films Of π-Conjugated Systems: Litera...mentioning
confidence: 65%
“…Because a phenylene spacer between two thiophene units does not introduce any tilt angle or deviation from planarity, aggregate ECD spectra of thiophene/phenylene copolymers are similar to those of already described PTs; they are dominated by exciton couplings between substantially planar polymer chains, although with less pronounced vibrational structure than PTs. Instead, aggregate ECD spectra of poly­( p -phenyleneethynylene- alt -bithiophene)­s resemble those of PPEs, with the characteristic sequence of several sharp bands due to the exciton coupling between vibronic excitations . In 2012, a series of axially chiral 1,1′-binaphthyl-thiophene copolymers were synthesized and investigated as drop-casted films by Goto et al, while Hirahara and colleagues focused the attention on alternating fluorene-thiophene copolymers, reporting dissymmetry factor g abs values up to 0.3 for pristine spin-coated samples; these giant ECD should be ascribed to the same extrinsic phenomena described above for poly­(fluorene)­s (section ). More recently, Bazan and co-workers described an alternating copolymer with thiophene or cyclopentadithiophene units and benzotriazole units bearing enantiopure ( S )-2-ethylhexyl chains, which showed maximum g abs factor of −0.008 at 665 nm in thin films prepared by drop casting of a chlorobenzene solution .…”
Section: Ecd Properties In Thin Films Of π-Conjugated Systems: Litera...mentioning
confidence: 65%
“…Chiral assemblies with controllable ICDs open up new perspectives in the field of chiroptical applications, including but not limited to optical amplifier materials, 23,36,37 chiral sensing, 38,39 optical switch, and data storage applications. [40][41][42] Furthermore, a research group in Spain has shown that the supramolecular gels can be applied as organic reaction media.…”
Section: Discussionmentioning
confidence: 99%
“…Another challenge is that for some chiral foldamers, the response to solvent media is insensitive, and only massive volume fraction (such as 10 vol % to 50 vol %) could arouse considerable changes. [38][39][40][41] Given the well-established solvatochromism theory and solvatochirochromism mentioned above, [42][43][44][45][46] the development of compounds with such properties and their ultrasensitive responsivity still remains unprecedented (Scheme 1a).…”
Section: Introductionmentioning
confidence: 99%
“…This issue, though has long been ignored, is of vital importance in understanding the structure‐chirality correlation, manipulating the chiroptics in a kinetic manner, and screening chiroptically active organic materials towards diversified applications. Another challenge is that for some chiral foldamers, the response to solvent media is insensitive, and only massive volume fraction (such as 10 vol % to 50 vol %) could arouse considerable changes [38–41] . Given the well‐established solvatochromism theory and solvatochirochromism mentioned above, [42–46] the development of compounds with such properties and their ultrasensitive responsivity still remains unprecedented (Scheme 1a).…”
Section: Introductionmentioning
confidence: 99%